Pentingnya Desain Ulang Pekerjaan Dan Deskripsi Pekerjaan Untuk Peningkatan Kinerja Pegawai Pada Masa Pandemi Covid 19 - Nafiudin; Andari; Denny Kurnia; Andini Tia Safitri (Sains Manajemen : Jurnal Manajemen UNSERA, 2021)
This study is to examine the effect of Job Redesign and Job Description on Employee Performance in the Public Works and Spatial Planning Office of Serang Regency. The method used is a quantitative method. The population is 55 employees and the sample is 35 employees. Data were collected using a questionnaire. To test the model and hypothesis, the SPSS version 25 program was used. Based on the results of this study indicate: Job Redesign partially has no effect on employee performance. Job description partially positive and significant effect on employee performance. Job redesign and job description simultaneously have a positive and significant effect on employee performance.